Peran Dosen dalam Meminimalisasi Perilaku Plagiasi Mahasiswa - Risa Rosalia; A. Jauhar Fuad (Indonesian Journal of Islamic Education Studies (IJIES), 2019)
This study aims to determine the role of lecturers in minimizing plagiarism behavior of students. This study uses a qualitative method with interview and documentation data collection techniques. The results of the study found that : (1) socialization to students related to plagiarism, providing understanding of writing scientific papers and understanding of plagiarism, (2) students are required to revise their writing indicated plagiarism, (3) students who do plagiarism do not get assignments, (4) improve students reading culture; (5) teaches students about sentences paraphrasing, encourages indirect qoutations, provides journal references for students; (6) requires students to actively participate in discussion forums; (7) calls for retention from print books; (8) requires students to take online classes; (9) check plagiarism online; (10) giving assignments by hand; (11) determine the limit of plagiarism tolerance in accordance with the guidelines for writing scientific papers.